Health policy analysis : framework and tools for success - Seavey, John W.; Aytur, Semra A.; McGrath, Robert J., 1967- (Springer Publishing Company, 2014)
This is the only resource to provide a step-by-step framework and expert guidance for preparing a policy analysis final paper or a capstone project for courses in health policy and health policy analysis. Building on a blend of theory and practical considerations for creating a successful policy analysis, the text guides students through the process of building an analysis that encompasses policy background, issue statement, normative and stakeholder analysis, criteria for success, systematic review of policy options, recommendation, and strategy for adoption.